Peran Pembelajaran Kooperatif dalam Meningkatkan Hasil Belajar dan Partisipasi Aktif Siswa di Dalam Kelas - Patrisius liber; Marni Marni; Andreas Teko; Lisna Novalia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Cooperative learning is an approach that has been proven effective in increasing student engagement and collaboration skills. Although it offers many advantages, its implementation often faces various challenges faced by both teachers and students. These challenges include differences in ability between students in a group, lack of active participation from some students, dominance of certain students in discussions, and difficulties in evaluating learning outcomes fairly. In addition, low student motivation and limited time and technology are also obstacles in implementing cooperative learning. To overcome these problems, it is important for teachers to manage groups well, develop leadership skills among students, and implement fair assessments both individually and in groups. Effective use of technology and ongoing training for teachers are also essential to support the success of cooperative learning.